2020
DOI: 10.46827/ejes.v7i10.3292
|View full text |Cite
|
Sign up to set email alerts
|

Employing Action Research for Professional Development of Efl College Teachers in the Mekong Delta, Vietnam

Abstract: The paper aimed to examine the perceptions and reality of English teachers at community colleges in the Mekong Delta in using action research as a tool for their professional development. The questionnaire and interviews were employed to collect the research data. The results showed that most EFL teachers recognized the significance of doing action research in developing their profession and many difficulties related to it were also reported. Some suggestions were figured out to help teachers conduct more rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Other researchers found that English language teachers neglect reflective teaching due to the more work load it requires [ 78 ]. The results of Van's study [ 86 ] showed that despite the recognized importance of action research, as a form of PF, there were a number of difficulties encountering its implementation.…”
Section: Results Of the Studymentioning
confidence: 99%
“…Other researchers found that English language teachers neglect reflective teaching due to the more work load it requires [ 78 ]. The results of Van's study [ 86 ] showed that despite the recognized importance of action research, as a form of PF, there were a number of difficulties encountering its implementation.…”
Section: Results Of the Studymentioning
confidence: 99%
“…Abelardo, Lomboy, Lopez, Balaria, and Subia (2019) surveyed 52 teachers in National High School and found that teachers cannot conduct research and report study findings due to a lack of related research training. In Vietnam, several studies on educational action research in administrators and teachers have been conducted so far such as (Anh, 2017;Hien, 2009;Van, 2020). A study by Anh (2017) on 30 teachers in central Vietnam showed that 74% of teachers felt confident to conduct action research, and 90% of those developed the knowledge after participating in an action research course.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, teachers could learn and enhance their teaching processes. Van (2020) showed that action research played an essential role in teacher professional development.…”
Section: Introductionmentioning
confidence: 99%